Self-reinforcing effects between housing prices and credit: an extended version - André K. Anundsen; Eilev S. Jansen (Statistics Norway, Research Department, 2013)
The financial crisis has brought the interaction between housing prices and household borrowing into the limelight of economic policy debate. This paper examines the nexus of housing prices and credit in Norway within a structural vector equilibrium correcting model (SVECM) over the period 1986q2- 2008q4. The results establish a two-way interaction in the long-run, so that higher housing prices lead to a credit expansion, which in turn puts an upward pressure on housing prices. Interest rates influence housing prices indirectly through the credit channel. Furthermore, households' expectations about future development in teir own income as well as in the Norwegian economy have a significant impact on housing price growth. Dynamic simulations show how shocks are propagated and amplified. When we augment the model to include the supply side, these effects are dampened. The paper is an extended version of Anundsen and Jansen (2013b) and it encompasses a previous Discussion Paper 651 (Anundsen and Jansen, 2011).
Keywords: C32; C52; E27; E44; G21; G28; R21; R31; 330; Housing prices; Household borrowing; Financial accelerator; Dynamic simulations